Allied health professionals: A promising ally in the work against health inequalities- A rapid review - A. Gkiouleka; M.R.J. Aquino; O. Ojo-Aromokudu; K.R. van Daalen; I.L. Kuhn; E. Turner-Moss; K. Thomas; R. Barnard; R. Strudwick; J. Ford (Elsevier, 2022)
Objectives: Allied Health Professionals (AHPs) have a crucial role in reducing health inequalities. However, there is a lack of evidence regarding the ways they can fulfil this role. This rapid review explores the ways in which AHPs can decrease health care or health outcome inequalities; address inequalities in the social determinants of health; and support disadvantaged groups at an individual, organisational and system level. Study design: Rapid review following Cochrane criteria and narrative synthesis. Methods: MEDLINE, EMBASE, CINAHL, Web of Science and AMED were searched combined with grey literature, to identify quantitative or qualitative review articles published between January 2010 and February 2021. Results: From 8727 references, 36 met the inclusion criteria. The methodological quality of the studies was assessed with the AMSTAR tool and was generally low. Meta-analysis was not possible due to the heterogeneity of the studies, and a narrative synthesis was produced. Three themes emerged at patient and organisational level: 1) access to AHP services; 2) quality of care; and 3) social determinants of health. Two themes emerged at system level: 1) unequal workforce distribution and 2) lack of inclusive clinical guidelines. Conclusions: This rapid review offers a broad range of evidence on the ways AHPs can contribute to the reduction of inequalities in health care, both in terms of access and quality of care and in health outcomes. More research is needed to further understand the impact of AHPs on inequalities affecting specific groups and their contribution to equitable distribution of social determinants of health.